2013
DOI: 10.1093/mnras/stt1188
|View full text |Cite
|
Sign up to set email alerts
|

The nature of extremely red galaxies in the local universe

Abstract: We investigate the nature of extremely red galaxies (ERGs), objects whose colours are redder than those found in the red sequence present in colour-magnitude diagrams of galaxies. We selected from the Sloan Digital Sky Survey Data Release 7 a volumelimited sample of such galaxies in the redshift interval 0.010 < z < 0.030, brighter than M r = −17.8 (magnitudes dereddened, corrected for the Milky Way extinction) and with (g − r) colours larger than those of galaxies in the red sequence. This sample contains 416… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…We correct for internal reddening, considering that it has been demonstrated that galaxies with high SFRs and high dust content may contaminate the green valley artificially, not representing an actual state of transitioning between populations (e.g. Sodré et al 2013;Gonçalves et al 2012). To do so, we followed the Calzetti et al (2000) dust correction procedure for UV-optical colours, based on the Balmer decrement.…”
Section: Dust Attenuationmentioning
confidence: 99%
“…We correct for internal reddening, considering that it has been demonstrated that galaxies with high SFRs and high dust content may contaminate the green valley artificially, not representing an actual state of transitioning between populations (e.g. Sodré et al 2013;Gonçalves et al 2012). To do so, we followed the Calzetti et al (2000) dust correction procedure for UV-optical colours, based on the Balmer decrement.…”
Section: Dust Attenuationmentioning
confidence: 99%
“…The internal extinction of the galaxies in our sample has not been taken into account, therefore, it is likely that some contamination by reddened green-valley systems is present (for further reading on the extinction degeneracy, see Worthey 1994;De Meulenaer et al 2013;Sodré et al 2013, and references therein).…”
Section: The Final Samplementioning
confidence: 99%
“…Most blue star-forming galaxies are obscured by dust, occupying the redder parts of the galaxy colour-magnitude diagrams (CMD), both in the local Universe (Sodré et al 2013) and at higher redshifts (Gonçalves et al 2012). We correct u, g, and r SDSS magnitudes by intrinsic reddening, through the flux of Hα and H β emission lines (measurement details are described in Brinchmann et al 2004).…”
Section: Datamentioning
confidence: 99%